PELAKSANAAN UNDANG-UNDANG PERKAWINAN (Studi tentang Perkawinan di Bawah Umur dan Perkawinan Tidak Tercatat di Kabupaten Bangkalan) - Sri Hidayati; Zaenal Abidin (Harmoni, 2013)
The enforcement of the act number 1 year 1974 about the marriage in Indonesia has been occurred for 38 years, but the implementation is yet completely run well especially for the rule of the minimum age restriction of the marriage and the registration of the marriage. Several factors that cause of the amount under age marriage which is defined in the marriage act of Bangkalan, 19 for men and 16 for women, are culture, education and economical factor. Besides, one of the factors that cause of the unregistered marriage is the lack of the society’s knowledge of how important marriage registration is, as well as for polygamy issue.